Coronally Advanced Flap with Connective Tissue Graft for Covering the Uncovered-A Case Report - Sah, Sunita; Shrestha, Sajeev (Orthodontic Journal of Nepal, 2024)
Tooth malposition is an important cause of gingival recession. Teeth that are labially rotated or tilted have thinner labial bony plate that is located further apically than adjacent teeth. Gingival margin also recedes to follow the contour of the bone which leads to root exposure causing compromised aesthetics, dentinal hypersensitivity and, carious and non-carious cervical lesions. Such defects if left untreated may exacerbate the condition causing premature loss of specific tooth/teeth. Therefore, periodontal and orthodontic treatment both is needed. However, orthodontic treatment on tooth with thin gingival tissue and recession may further deteriorate the periodontal tissue. Therefore, periodontal preparation before orthodontic treatment is essential to support the periodontal structures. Such periodontal defects can be corrected by gingival augmentation. Coronally advanced flap with connective tissue graft provides the most favorable clinical outcome. Thus, this combination is considered as the reference therapy for covering the exposed root surface.